Consumers’ perception of fair trade coffee in Australia and Japan - Tamaki, Rino (Curtin University, 2013)
Beyond the issues of food safety, a competitive price and the experiential quality attributes, consumers are becoming more concerned about the sustainable manner in which their food has been produced. This study explores differences in consumer’s perceptions, attitudes and behaviour towards Fair Trade (FT) and organic certification between Australian and Japanese coffee consumers. Overall, the credence attributes were a secondary consideration when respondents purchased coffee for either home consumption or from a café or restaurant.